2020
DOI: 10.1097/mao.0000000000002606
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive Cholesteatomas on Non-Echoplanar Diffusion-Weighted Magnetic Resonance Imaging

Abstract: Objectives: To investigate false-positive findings on nonechoplanar (non-EPI) diffusion-weighted magnetic resonance imaging (DWI) in patients under surveillance post-cholesteatoma surgery. Study Design, Setting, Subjects, and Methods: A retrospective review was performed on patients diagnosed with cholesteatoma who underwent surgical resection and were then followed by serial non-EPI DWI using half-Fourier acquisition single-shot turbo spin echo (HASTE) sequence. All patients had at least two annual follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Nevertheless, false-positives have been reported, related to abscess, wax/debris, and encephaloceles. 25 False-negatives, too, occur, particularly in small (,3-5 mm) lesions. [26][27][28] Horn et al, 27 for example, concluded that non-EPI DWI does not eliminate the need for second-look surgery due to the rate of false-negative examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, false-positives have been reported, related to abscess, wax/debris, and encephaloceles. 25 False-negatives, too, occur, particularly in small (,3-5 mm) lesions. [26][27][28] Horn et al, 27 for example, concluded that non-EPI DWI does not eliminate the need for second-look surgery due to the rate of false-negative examinations.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the good resolution and the lower incidence of interface artifacts in thin-section coronal fast spin-echo–based non-EPI techniques, few cases of false negatives and false positives have still been observed. While false negatives are mainly due to very small lesion size, false positives can be due to several different condition that could enhance the presence of MRI artifacts (i.e., presence of prosthetic materials or metallic dental implants, recent surgery, admixed otomastoiditis with areas of abscessualisation) ( 1 , 23 , 24 ). To overcome possible pitfalls and implement the interpretation of indeterminate single-plan DWI, additional axial DWI can be a worthwhile information support.…”
Section: Discussionmentioning
confidence: 99%
“…One study, specifically focusing on false positives in the adult population, reported that in three of the four false positive cases, areas of high avidity disappeared on subsequent imaging. 17 They reported false positives to be related to cartilage grafts. 17 Within our study, one of the false positives was reported as 'possible cholesteatoma' and did not have symptoms at the time of diffusion-weighted MRI; this patient could possibly have been followed up with subsequent imaging.…”
Section: Cwd = Canal Wall Downmentioning
confidence: 99%
“…17 They reported false positives to be related to cartilage grafts. 17 Within our study, one of the false positives was reported as 'possible cholesteatoma' and did not have symptoms at the time of diffusion-weighted MRI; this patient could possibly have been followed up with subsequent imaging. However, the other four patients were reported as 'probable cholesteatoma' or 'definite cholesteatoma', and three of the four had symptoms, making any decision not to operate challenging.…”
Section: Cwd = Canal Wall Downmentioning
confidence: 99%